Death and the Migrant Bodies, Borders and Care - Gunaratnam, Yasmin (Bloomsbury Academic, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Death and the Migrant is a sociological account of transnational dying and care in British cities. It chronicles two decades of the ageing and dying of the UK's cohort of post-war migrants, as well as more recent arrivals. Chapters of oral history and close ethnographic observation, enriched by photographs, take the reader into the submerged worlds of end-of-life care in hospices, hospitals and homes. While honouring singular lives and storytelling, Death and the Migrant explores the social, economic and cultural landscapes that surround the migrant deathbed in the twenty-first century. Here, everyday challenges - the struggle to belong, relieve pain, love well, and maintain dignity and faith - provide a fresh perspective on concerns and debates about the vulnerability of the body, transnationalism, care and hospitality. Blending narrative accounts from dying people and care professionals with insights from philosophy and feminist and critical race scholars, Yasmin Gunaratnam shows how the care of vulnerable strangers tests the substance of a community. From a radical new interpretation of the history of the contemporary hospice movement and its 'total pain' approach, to the charting of the global care chain and the affective and sensual demands of intercultural care, Gunaratnam offers a unique perspective on how migration endows and replenishes national cultures and care. Far from being a marginal concern, Death and the Migrant shows that transnational dying is very much a predicament of our time, raising questions and concerns that are relevant to all of us.